Keeping It Real: Infection Prevention and Control Problems and Solutions in Low- and Middle-income Countries. Issue 3 (8th February 2022) - Dramowski, Angela; Bekker, Adrie; Anugulruengkitt, Suvaporn; Bayani, One; Martins Gonçalves, Fernanda; Naizgi, Mulugeta; Magnino, Aline; Puthanakit, Thanyawee; Salle, Fernanda; da Silva, André Ricardo Araujo; Molyneux, Elizabeth; Strysko, Jonathan; et al.
Abstract : Infection prevention challenges are ubiquitous in healthcare, but some are unique to or more prevalent in low-and middle-income country settings. Despite limited resources, innovative and committed paediatric healthcare providers and infection preventionists have found creative solutions to address the very real and pressing risks their patients face every day. We gathered examples of infection prevention and control challenges faced by clinicians in resource-limited healthcare facilities, and the real-world infection prevention and control solutions they implemented, with the goal of learning broader lessons applicable to low-and middle-income countrie.